Food Shopping Behavior: A Long Way to Prevent Food Waste - Mahestu N Krisjanti; Agnes Gracia Quita (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
Food sustainability is becoming big concern these last couple years, due to the food scarcity issues in many countries. Â However in contrary previous studies reported the food waste behavior is getting bigger at this moment because of over food preparation, food stocking, undesired food, and food packaging. Over all, most of these issues come from the food shopping behavior. People tend to buy more food products than what they need. Therefore, the determinant of food shopping behavior is urgently found in order to find the solution to drive people to have planned food buying behavior. This research elaborates how motivation to prevent food waste would affect food shopping behavior. The data collection through survey has been done in the young adult community. The finding indicates that having motivation to prevent food waste will contribute to well-planned food shopping behavior. Furthermore, the research also indicates that female shows higher motivation in preventing food waste as also reported in some previous studies that report similar result.